Laboratory Evaluation of Flight Capacities of Aedes japonicus (Diptera: Culicidae) Using a Flight Mill Device. Issue 6 (4th December 2021) - Krupa, Eva; Gréhal, Alexa-Lou; Esnault, Jérémy; Bender, Christelle; Mathieu, Bruno
Abstract: Dispersion expands the distribution of invasive species and as such, it is a key factor of the colonization process. Aedes japonicus japonicus (Theobald, 1901) is an invasive species of mosquito and a vector of various viruses. It was detected in the northeast of France in 2014. The population of this species can expand its distribution by several kilometers per year. However, though flight capacities play an active part in the dispersion of Ae. japonicus, they remain unknown for this species. In this study, we investigated the flight capacities of Ae. japonicus in a laboratory setting using the flight mill technique. We evaluated the influence of age on flight. We recorded videos of individual flights with a camera mounted on Raspberry Pi. We extracted data on distance, duration, and speed of flight using the Toxtrac and Boris software. Our analysis showed a median flight distance of 438 m with a maximum of 11, 466 m. Strong flyers, which represented 10% of the females tested, flew more than 6, 115 m during 4 h and 28 min at a speed of 1.7 km per h. As suspected, Ae. japonicus is a stronger flyer than the other invasive species Aedes albopictus (Skuse, 1894) (Diptera: Culicidae). To our knowledge, this is the first flight mill study conducted on Ae. japonicus and therefore the first evaluation of its flight capacity. In the future, the flight propensity of Ae. japonicus determined in this study can be included as a parameter to model the colonization process of this invasive vector species.